PENGARUH AUDIT INTERNAL TERHADAP PENGENDALIAN INTERNAL PENJUALAN PADA PERUSAHAAN AIR MINUM DI KOTA BANDUNG - SATRIA, MUHAMMAD RIZAL; Mayasari, Aghnia Nur (LAND JOURNAL, 2024)
Internal Audit is a series of processes and technical personnel within a company that confirms the accuracy of financial information and activity procedures according to regulations. The purpose of this study was to determine internal audit control and sales control and to determine the effect of internal audit on internal sales control in the regional public company PT X, Bandung City. Internal audit also provides very objective information regarding the accuracy of sales data which will become the basis for management decision making. Sampling using purposive sampling. Collecting data using literature study, questionnaires. For data analysis techniques using validity test, reliability test, data normality test, Spearman rank correlation analysis. Simple linear regression analysis, Determination Coefficient Test, t test. The results showed that internal audit had a significant effect on internal control of sales at the public company in the PT X area, Bandung City.